Photophysics of Carbon Nanotubes Interfaced with Organic and Inorganic Materials - Levitsky, Igor A.; Euler, William B.; Karachevtsev, Victor A. (Springer London : Imprint: Springer, 2012)
Photophysics of Carbon Nanotubes Interfaced with Organic and Inorganic Materials describes physical, optical and spectroscopic properties of the emerging class of nanocomposites formed from carbon nanotubes (CNTs)  interfacing with organic and inorganic materials. The three main chapters detail novel trends in  photophysics related to the interaction of  light with various carbon nanotube composites from relatively simple CNT/small molecule assemblies to complex hybrids such as CNT/Si and CNT/DNA nanostructures.   The latest experimental results are followed up with detailed discussions and scientific and technological perspectives to provide a through coverage of major topics including: ·   Light harvesting, energy conversion, photoinduced charge separation  and transport  in CNT based nanohybrids · CNT/polymer composites exhibiting photoactuation; and ·         Optical  spectroscopy  and structure of CNT/DNA complexes. Including original data and a short review of recent research, Photophysics of Carbon Nanotubes Interfaced with Organic and Inorganic Materials makes this emerging field of photophysics and its applications available to academics and professionals working with carbon nanotube composites in fundamental and applied fields.